DERIVATIONAL AND INFLECTIONAL AFFIXES IN THE LANGUAGE OF JAKARTA GLOBE NEWS ARTICLES - Anita Sari; Latifah Latifah; Ismi Adinda; Wirhayati Wirhayati; Kanaya Ratu Vanisa (Universitas PGRI Palembang, 2026)
Understanding the morphological structure of English words remains a challenge for many learners, particularly students of English at Universitas Pamulang, who often experience difficulties in identifying bound morphemes attached to root or base words to create new lexical items or indicate grammatical functions. This study investigates the use of derivational and inflectional affixes in the language of Jakarta Globe news articles. Employing a qualitative descriptive approach, the research is grounded in Yule’s (2006) theory of English morphology. The data were obtained from the online Jakarta Globe news article entitled Indonesia Introduces AI and Coding to 59,000 Schools Nationwide. Data collection involved identifying words containing affixes and classifying them into derivational and inflectional categories based on their morphological functions. The analysis revealed that inflectional suffixes were the most frequently occurring morphological forms, accounting for 27 instances (50%), including -s, -er, -ed, and -ing. Derivational suffixes appeared in 25 instances (46%), comprising -ence, -ive, -ion, -ity, -ly, -ation, -al, -ment, -ary, -ic, and -tion. No inflectional prefixes were identified in the data. In contrast, derivational prefixes occurred only twice (4%), represented by infra- and under-. These findings indicate that inflectional suffixes are the predominant morphological features in the language of the selected Jakarta Globe news article, highlighting their significant role in expressing grammatical relationships, whereas derivational affixes occur less frequently and primarily contribute to lexical expansion and word formation.